Small-Scale Perfusion Bioreactor of Red Blood Cells for Dynamic Studies of Cellular Pathways: Proof-of-Concept - Prudent, Michel; Stauber, Frédéric; Rapin, Alexis; Hallen, Sonia; Pham, Nicole; Abonnenc, Mélanie; Marvin, Laure; Rochat, Bertrand; Tissot, Jean-Daniel; Lion, Niels (Frontiers in Molecular Biosciences, 2016)
To date, the development of bioreactors for the study of red blood cells (RBCs, daily transfused in the case of disease or hemorrhage) has focused on hematopoietic stem cells. Despite the fact that mature RBCs are enucleated and do not expand, they possess complex cellular and metabolic pathways, as well as post-translation modification signaling and gas-exchange regulation. In order to dynamically study the behavior of RBCs and their signaling pathways under various conditions, a small-scale perfusion bioreactor has been developed. The most advanced design developed here consists of a fluidized bed of 7.6 mL containing 3·109 cells and perfused at 8.5 μL/min. Mimicking RBC storage conditions in transfusion medicine, as a proof-of-concept, we investigated the ex vivo aging of RBCs under both aerobic and anaerobic conditions. Hence, RBCs stored in saline-adenine-glucose-mannitol (SAGM) were injected in parallel into two bioreactors and perfused with a modified SAGM solution over 14 days at room temperature under air or argon. The formation of a fluidized bed enabled easy sampling of the extracellular medium over the storage period used for the quantitation of glucose consumption and lactate production. Hemolysis and microvesiculation increased during aging and were reduced under anaerobic (argon) conditions, which is consistent with previously reported findings. Glucose and lactate levels showed expected trends, i.e., decreased and increased during the 2-week period, respectively; whereas extracellular glucose consumption was higher under aerobic conditions. Metabolomics showed depletion of glycolsis and pentose phosphate pathway metabolites, and an accumulation of purine metabolite end-products. This novel approach, which takes advantage of a fluidized bed of cells in comparison to traditional closed bags or tubes, does not require agitation and limit shear stress, and constantly segragates extracellular medium from RBCs. It thus gives access to several difficult-to-obtain on- and off-line parameters in the extracellular medium. This dynamic bioreactor system does not only allow us to probe the behavior of RBCs under different storage conditions, but it also could be a powerful tool to study physiological or pathological RBCs exposed to various conditions and stimuli.